More Kiwi music : upgrading New Zealand's music industry through successful music export : a 152.800 (100 point) masters thesis presented in partial fulfilment of the requirements for the degree of Master in Business Management at Massey University, New Zealand - Kirchner, Astrid Susan (Massey University, 2007)
The purpose of this study is to explore the operation of the New Zealand music industry and the activities its participants could undertake to upgrade success in music export. To do this it describes the local and international factors which influence the industry and how its participants operate and broadly outlines the global background against which these activities take place. The thesis looks at the theoretical underpinning of the marketing strategies used by record companies and artists and the nature of the contractual agreements that release partners enter into before releasing and marketing a product. In particular, the nature of these agreements is examined in relation to the specific circumstances involved in exporting a musical product, whether artist, copyright or physical product. This examination is aided by descriptions of exactly what constitues 'success' in the music industry and how difficult it is to quantify this success in an arts based industry that revolves largely around people acting as 'products'. Against this background a description of the specific characteristics of the New Zealand music industry and its key institutions and participants, as well as results gathered from a questionnaire, enable the thesis to show the similarities of New Zealand to the global market. These similarities involve major label domination of the local market, the impact of technological advances and the traditional means and strategies of music export. Detailed comparison and description of the New Zealand music industry to those of Australia and Canada allows the researcher to highlight areas of potential strength and weakness within the local music industry that are potentially beneficial or detrimental to the local industry's ability to export product successfully. Finally, the thesis draws upon the insights gained from the study in making recommendations to the New Zealand Government regarding further research and strategies that could potentially benefit the future growth of New Zealand music export.
Keywords: New Zealand; Music trade; Musicians